A simple & Rapid Method For Detecting Bacterial Myrosinase Corresponding Protein Band - Albaser, Abdulhadi; Luang-IN, Vijitra; Nisar, Numrah; Abd Kadir, Nurul; Rossiter, John (Journal of Pure & Applied Sciences, 2023)
Myrosinases have significant scientific and medical implications. Unfortunately, detection and purification of myrosinase from microbes requires the use of highly cost substrates (glucosinolates) such as sinigrin and expensive instruments such as Fast Protein Liquid Chromatography and or ion exchange chromatography. In this work, we used only 20 mL of bacterial culture supplemented with sinigrin (10 mM) to obtain partially purified myrosinase. The crude protein extract was loaded onto native polyacrylamide gel and putative myrosinase band was identified and eluted. This step successfully minimised the numbers of protein bands of bacterial crude extracts to be further analysed. The current method describes a simple, rapid and cost effective protocol for isolation and detection of active bacterial myrosinases. Furthermore, our method can be used as a purification step.